Sleeping - Tinna Laufey Asgeirsdottir; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2008)
Sleep is a source of energy. This energy is available in limited quantity and individuals must decide when it should be renewed and when it should be consumed. The economics of sleeping and the economics of resource extraction are one and the same. More specifically, utility maximization with respect to sleep satisfies Hotelling's rule on the optimal utilization of natural resources. Several applications emerge from the analysis. These include the effects of labor-market opportunities on sleep patterns; the effect of having children; the consequences of the decreased division of labor within the household; and the relationship between sleep deprivation and obesity.
Keywords: D11; D13; I12; J12; J13; J22; J24; Q20; 330; Sleep; productivity; children; health; human capital; Haushaltsökonomik; Hotelling-Regel; Humankapital; Gesundheit; Fertilität; Produktivität; Theorie